Large-scale reuse through a novel software representation - Hoi, Chin Pang. (2008)
My project is based on a novel software representation, called the software event net (the SE-Net), which aims to address the above-mentioned problem. The SE-Net is based on the high-level Petri net with some modification and extension for the specification of events produced in software systems.